2011
DOI: 10.1038/bjc.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically silenced miR-34b/c as a novel faecal-based screening marker for colorectal cancer

Abstract: Background:MicroRNAs are tiny non-coding small endogenous RNAs that regulate gene expression by translational repression, mRNA cleavage and mRNA inhibition. The aim of this study was to investigate the hypermethylation of miR-34b/c and miR-148a in colorectal cancer, and correlate this data to clinicopathological features. We also aimed to evaluate the hypermethylation of miR-34b/c in faeces specimens as a novel non-invasive faecal-DNA-based screening marker.Methods:The 5-aza-2′-deoxycytidine treatment and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 48 publications
2
67
0
2
Order By: Relevance
“…Blood is regarded as an ideal type of sample for cancer biomarker discovery as it can be collected easily in a minimally invasive manner [22]. Some studies have also attempted to use miRNAs from feces as markers for gastrointestinal cancer [23,24]. The use of different sample types enables the discovery of novel markers under various constraints.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Blood is regarded as an ideal type of sample for cancer biomarker discovery as it can be collected easily in a minimally invasive manner [22]. Some studies have also attempted to use miRNAs from feces as markers for gastrointestinal cancer [23,24]. The use of different sample types enables the discovery of novel markers under various constraints.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…On the other hand, our data and others [25,27,28,[54][55][56][57][58][59][60][61][62][63][64][65][66] have shown that quantitative changes in the expression of few miRNA genes in stool or blood that are associated with colon cancer permit development of more sensitive and specific CRC molecular markers than those currently available on the market. In comparison to the commonly employed FOBT stool test, a noninvasive molecular and reliable test would particularly be more convenient as there would be no requirement for dietary restriction, or meticulous collection of samples, and thus a screening test would be acceptable to a broader segment of the population.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 60%
“…It should be emphasized that although not all of the shed cells in stool are derived from a tumor, data published by us and others [25,27,28,[56][57][58][59][60][61][62][63][64][65][66][67][68] have indicate that diagnostic miRNA gene expression profiles are associated with adequate number of exfoliated cancerous cells and enough transformed RNA is released in the stool, and also the availability of measurable amount of circulating. miRNA genes in blood (either cellular or extracellularly), which can be determined quantitatively by a sensitive technique such as PCR in spite of the presence of bacterial DNA, non-transformed RNA and other interfering substances.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 99%
See 2 more Smart Citations